Hřebování pertrochanterických zlomenin - operační technika - Skála-Rosenbaum, J; Douša, P; Bartoška, R (Rozhledy v chirurgii, 2013)
Nailing of pertrochanteric fractures is indicated when DHS is associated with high rate of complications. Thus in unstable comminuted fractures, mainly with posterolateral defect and instability, with Adam´s arch defect and medial instability and in cases when fracture line extends into the subtrochanteric region. The increase in number of nailed pertrochanteric fractures has both its rational and irrational reasons; irrational, as until now there is no clear evidence, that nailing is a faster, safer and easier procedure with a lower rate of complications compared with DHS, a rational, as a proven increase in number of unstable and comminuted fractures has to be reflected in treatment changes. Thus, with respecting the operative techniques principles, intramedullary nailing provides evident biomechanical advantages with the possibility of full weight-bearing and a very low rate of complications.
Keywords: intramedulární fixace fraktury; fraktury kyčle; Hip Fractures; Humans; lidé; Fractures, Comminuted; tříštivé fraktury; Fracture Fixation, Intramedullary